Interactions between periodontal bacteria and human oral epithelial cells: Fusobacterium nucleatum adheres to and invades epithelial cells - Han, Y W; Shi, W; Huang, G T; Kinder Haake, S; Park, N H; Kuramitsu, H; Genco, R J (Infection and immunity, 2000)
Bacteria are causative agents of periodontal diseases. Interactions between oral bacteria and gingival epithelial cells are essential aspects of periodontal infections. Using an in vitro tissue culture model, a selected group of gram-negative anaerobic bacteria frequently associated with periodontal diseases, including Bacteroides forsythus, Campylobacter curvus, Eikenella corrodens, Fusobacterium nucleatum, Porphyromonas gingivalis, and Prevotella intermedia, were examined for their ability to adhere to and invade primary cultures of human gingival epithelial cells (HGEC). The effects of these bacteria on the production of interleukin-8 (IL-8), a proinflammatory chemokine, were also measured. These studies provided an initial demonstration that F. nucleatum adhered to and invaded HGEC and that this was accompanied by high levels of IL-8 secretion from the epithelial cells. The attachment and invasion characteristics of F. nucleatum were also tested using KB cells, an oral epithelial cell line. The invasion was verified by transmission electron microscopy and with metabolic inhibitors. Invasion appeared to occur via a "zipping" mechanism and required the involvement of actins, microtubules, signal transduction, protein synthesis, and energy metabolism of the epithelial cell, as well as protein synthesis by F. nucleatum. A spontaneous mutant, lam, of F. nucleatum, isolated as defective in autoagglutination, was unable to attach to or invade HGEC or KB cells, further indicating the requirement of bacterial components in these processes. Sugar inhibition assays indicated that lectin-like interactions were involved in the attachment of F. nucleatum to KB cells. Investigation of these new virulence phenotypes should improve our understanding of the role of F. nucleatum in periodontal infections.